Occupational sex segregation and discrimination in peninsular Malaysia - Latifah Mohamad Nor, (Penerbit Universiti Kebangsaan Malaysia, 2000)
This paper examines the occupational effects on gender earnings differentials by examining the earnings of women in each major occupational category and comparing their labor market outcomes to those of men. Using Malaysian data, the results indicate that gender earnings differentials are found to vary within occupations, which contributes to the overall gender earnings gap in this country. The earning of men and women are found to be lower in jobs held exclusively by women in clerical occupations than the earnings of men and women employed in predominantly male occupations in sales, which suggest that occupational earnings are significantly affected by the percentage of women in an occupation. This study also reveals that the earnings gap seems to be smallest in clerical occupations, which has the highest percentage of women, and this gap is largest in occupations with the smallest percentage of women, such as in sales. Besides differences of endowment factors, discrimination also plays an important role that affects gender earnings differentials within each occupation. Except for clerical occupations, human capital variables have a smaller contribution compared to the discrimination component in explaining gender earnings differentials for each occupational category. All of these discriminatory earnings differentials were attributable to favorable male treatment rather than unfavorable female treatment